Livestock Productivity and Desertification in the Arid Lands of Western Rajasthan - Kalla, Jagdeesh C; Ghosh, Pulak K; Joshie, B R (Annals of Arid Zone, 2016)
The livestock sector is of considerable economic significance for the arid districts of western Rajasthan. However, the observed increase in livestock productivity over the years is mo~e a reflection of the increased number of livestock than any increase in the efficiency of individual productivity. Further, the high growth rate of livestock has been depleting the region of its phytomass resources resulting in ecological imbalances. Simultaneously, increased utilisation of marginal lands for crop growing has been further accentuating the desertification process. Optimization of livestock production through checks on excessive animal population build-up and use of marginal lands for increased fodder production has been advocated as a means to reducing the impact of the forces of desertification.